Analisis Laba Rugi Sebagai Dasar Pengambilan Keputusan Investasi - Arviyori (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2025)
This study analyzes the role of income statements as a basis for investment decision-making. The research applies a quantitative descriptive and comparative approach using secondary data from manufacturing companies listed on the Indonesia Stock Exchange over the last five years. Findings indicate that stable net income over time is more attractive to investors, as it signals sustainable business performance and reliable management. Furthermore, profit margin indicators such as gross profit margin, operating margin, and net profit margin significantly influence investors’ perceptions of company profitability and long-term growth prospects. The results also show that income statement analysis is closely related to stock price movements, where a decline in profits often corresponds to negative market reactions, while consistent growth generates positive responses. However, the study highlights the limitations of relying solely on income statements, as they do not reflect cash flow conditions or external economic factors. Thus, comprehensive investment decisions require integrating income statement analysis with other financial reports and macroeconomic considerations. Overall, this study concludes that income statement analysis remains a crucial foundation for rational and objective investment decision-making. Nevertheless, investors are advised to combine it with broader financial and contextual analyses to ensure more accurate and sustainable outcomes in investment practices.